A STUDY OF RETAINING MILLENNIAL EMPLOYEES OF PT. BFI FINANCE INDONESIA TBK, BRANCH MANADO - Mawuntu, Kezia; Saerang, David P.E.; Tielung, Maria V.J. (Universitas Sam Ratulangi, 2019)
Abstract: Millennial bad characteristics when they enter into world of work such as they do not want to work under pressure, like to shifting work, feel disappointed if opportunity of career development is not available and etc. This is become the problem of company in order to retain the millennial employee to stay work in company. This research aims to know how the company strategy to retaining the millennial employees of PT. BFI Finance Indonesia Tbk, Branch Manado. This research used qualitative method with purposive sampling technique. The sample is uses 20 millennial employees as informant. The data collected by doing in-depth interview. The result shows that from 6 indicators of company strategies only 3 indicators that become the most influential of retaining the millennial employees of PT. BFI Finance Indonesia Tbk, Branch Manado which are work environment, career development and teamÂ relationship. The company should maintaining these all indicators so the millennial employees feel loyal to working in the company therefore it can help to reduce the company turnover rate.Â Keywords: human resource, retaining millennial employees